APLIKASI PROSES TEMPERING UNTUK OPTIMASI TITIK LELEH COKELAT HITAM PRODUK PENGOLAHAN PINTAS - Subandrio, A. Sofian Nasori Astuti, Lamhot P. Manalu (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
This research is to study the effect of tempering conditions on the change of melting point of dark chocolate produced through a stage of heating and cooling with the stirring process at low-speed. Melting point, hardness, and stickiness were measured in the combination of three different tempering conditions: low temperature (29°C, 31°C, and 33°C), high temperature (45°C, 47.5°C, and 50°C), and tempering time (10 minutes, 17.5 minutes, and 25 minutes). Optimum tempering conditions were evaluated using Response Surface Method (RSM). The best tempering condition was obtained at the combination of low temperature at 31°C, high temperature at 47.5°C, and tempering time at 17.5 minutes. This combination resulted melting point, hardness, and stickiness at 36.5°C, 746.3 g, and -89.941 g respectively. Thus, attainment of optimum tempering condition was central to the desired properties of produce which melt at human body temperature with the minimum level of hardness at room temperature. The best chocolate product is easily melted at human body temperature, but it is hard at room temperature and also have a minimum adhesiveness cause. Keywords : chocolate, hardness, melting point, response surface method, tempering